Diagnostic of the situation [Part 1. Components of drought planning. 1.1. The planning framework] - Tsiourtis N.X. (Drought management guidelines technical annex, 2007)
Water shortages can be the result of drought phenomena but can be also the result of human actions such as increase of water demand due to population growth or changes of people habits, or due to bad water management plans. This chapter outlines the diagnostic search that water policy makers, water managers, decision makers and other stakeholders, should take before embarking on the preparation of drought preparedness plans, so that they know the causes of water shortage and that drought preparedness plans are necessary. If the results from this search are negative, the relevant authorities must take the necessary measures and actions so that the proper environment is created in each of the items so that the preparation and implementation of Drought Preparedness Plans is facilitated, and it is effective and efficient.